Analisis Penggunaan Activity Based Costing (ABC) dalam Menentukan Tarif Jasa Rawat Inap - Jainuddin Unsale; Hustianto Sudarwadi; Anik Wuriasih (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2022)
The hospital is one of the health services engaged in services. Hospitals in determining the cost of goods sometimes still use the traditional method. Where the preparation of this traditional cost of cost information presented still has a weakness that is distorted. The purpose of this study was to determine the rate of inpatient services using Activty Based Costing at the RS AL dr. Azhar Zahir Manokwari and find out the comparison of inpatient service rates that have RS AL dr. Azhar Zahir Manokwari uses it with Activity Based Costing. The analytical method used is descriptive qualitative method. Data collection techniques are interviews and documentation. The results showed that the calculation using Activity Based Costing gave different results. The results of calculations using the Activity Based Costing system compared to the rates determined by the hospital give more expensive results in all classes, namely VIP Class, Class 1, Class 2 and Class 3. The differences that occur between the traditional method and the Activity Based Costing method are caused by the imposition of overhead costs on each of these products.